2017
DOI: 10.1308/rcsann.2017.0122
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the choice of treatment modality for individual patients with varicose veins

Abstract: INTRODUCTION There is evidence of effectiveness for a range of different treatment modalities for varicose veins but limited information about factors that influence treatment choice for individual patients. METHODS A postal survey was sent to 438 UK members of the Vascular Society of Great Britain and Ireland. RESULTS Overall, 251 responses were received (response rate 57%). A total of 222 respondents treated varicose veins using conventional surgery (84%), endothermal ablation (82%) and foam sclerotherapy (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
0
6
0
1
Order By: Relevance
“…For physicians in the United Kingdom, there is a trend toward conventional surgery over endothermal ablation, presumably attributed to financial concerns within the NHS. 15 In the US, the variability in venous disease treatment has been attributed to a lack of uniformity in insurance policies. 2 Similarly, in China, a survey of venous surgeons found that the majority of practitioners endorse reimbursement and patient health insurance as significant factors in their treatment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…For physicians in the United Kingdom, there is a trend toward conventional surgery over endothermal ablation, presumably attributed to financial concerns within the NHS. 15 In the US, the variability in venous disease treatment has been attributed to a lack of uniformity in insurance policies. 2 Similarly, in China, a survey of venous surgeons found that the majority of practitioners endorse reimbursement and patient health insurance as significant factors in their treatment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to the NICE guideline, the DUS exam is necessary to confirm the diagnosis of primary or recurrent varicose veins, and to determine whether the cause of venous reflux is treatable according to the recommended treatments offered by the NICE guidelines (first endothermal ablation, then ultrasound-guided foam sclerotherapy and, when both are unsuitable, open repair surgery). 2 Therefore, in the UK, the DUS report usually includes the presence and distribution of truncal venous reflux, the diameter and course of incompetent veins, the distance of incompetent veins from the skin, as well as the presence and diameter of incompetent perforator veins. However, the diameter of the latest is mainly reported in those centres where their treatment is considered.…”
Section: Causes Of Inconsistency In Dus Reporting Performed In Patients With Varicose Veinsmentioning
confidence: 99%
“…КЕD позволяет улучшить кровообращение в тканях мозга, нормализовать память, усилить интеллектуальные способности [8,9]. При назначении пептида установлено повышение резистентности микрососудов кожного покрова у пациентов, имеющих в анамнезе гиповитаминоз [10,11]. Дополнительно выявлен процесс нормализации циркуляции крови по капиллярам у крыс, болеющих пародонтитом, при введении пептида KED в виде инъекций [8].…”
Section: оригинальная статья Original Articleunclassified